Effect Of Hydrogen Peroxide, Lactoperoxidase And Ultrasound On Microbiological Quality And Safety Of Raw Milk - Ahamed Kamal, Shamila Syuhada (2017)
Safety and quality of raw milk is of major concern in malaysia due to poor hygiene on the farms and the lack of cold chain for storage and during transportation of raw milk. The objectives of this study are to determine the microbiological quality and safety of raw milk produced by small dairy farms in penang; to evaluate the reliability of platform tests used at milk collection centers for assessment of quality and shelf life potential of raw milk; to determine the effects of different concentration of hydrogen peroxide (h2o2), lactoperoxidase system (nascn: h2o2 ratio) and effect of ultrasound on selected spoilage organisms and food-borne pathogens in milk. Raw milk obtained from 5 different farms had high total plate (tpc) (7.77 ± 0.33 log cfu ml’1), colifonns (3.40 ± 0.22 log cfu ml’1) and staphylococcus aureus (3.17 ± 0.14 log cfu ml'1) counts. Ninety percent of samples examined were positive for e. Coll. Salmonella serovars and listeria monocytogenes were detected in 5 and 3.33% of raw milk samples, respectively.